A New Three-Dimensional Reconstruction Method Using Algebraic Reconstruction Techniques - Niu, Aiqun; Han, Chia Yung; Wee, William G. (Journal of X-ray science and technology, 1990)
Three-dimensional image reconstruction plays a very important role in noninvasive diagnosis of biological systems and nondestructive evaluation of manufactured work-pieces. A new direct three-dimensional reconstruction algorithm, called TART (Three-dimensional ART), is presented in this paper. Oblique projection data are used and an ART-based algorithm is introduced to compensate for the limiting constraints of incomplete projection and/or limited angular coverage. The fact that oblique projection gives useful information to the reconstruction algorithm is shown mathematically. The algorithm can be used to solve the reconstruction problem under the conditions of both complete data and incomplete data. The algorithm first maps geometric information and projection data from an oblique plane into a horizontal plane, then calculates the weighting factors for the voxels based on this horizontal plane, and finally performs a 3-D ART reconstruction. Two experimental results illustrate the superiority of the algorithm over the previous reconstruction methods.